Neofunctionalization of Androgen Receptor by Gain-of-Function Mutations in Teleost Fish Lineage. (27th October 2015) - Ogino, Yukiko; Kuraku, Shigehiro; Ishibashi, Hiroshi; Miyakawa, Hitoshi; Sumiya, Eri; Miyagawa, Shinichi; Matsubara, Hajime; Yamada, Gen; Baker, Michael E.; Iguchi, Taisen
Abstract : Steroid hormone receptor family provides an example of evolution of diverse transcription factors through whole-genome duplication (WGD). However, little is known about how their functions have been evolved after the duplication. Teleosts present a good model to investigate an accurate evolutionary history of protein function after WGD, because a teleost-specific WGD (TSGD) resulted in a variety of duplicated genes in modern fishes. This study focused on the evolution of androgen receptor (AR) gene, as two distinct paralogs, ARα and ARβ, have evolved in teleost lineage after TSGD. ARα showed a unique intracellular localization with a higher transactivation response than that of ARβ. Using site-directed mutagenesis and computational prediction of protein–ligand interactions, we identified two key substitutions generating a new functionality of euteleost ARα. The substitution in the hinge region contributes to the unique intracellular localization of ARα. The substitution on helices 10/11 in the ligand-binding domain possibly modulates hydrogen bonds that stabilize the receptor–ligand complex leading to the higher transactivation response of ARα. These substitutions were conserved in Acanthomorpha (spiny-rayed fish) ARαs, but not in an earlier branching lineage among teleosts, Japanese eel. Insertion of these substitutions into ARs from Japanese eel recapitulates the evolutionary novelty of euteleost ARα. These findings together indicate that the substitutions generating a new functionality of teleost ARα were fixed in teleost genome after the divergence of the Elopomorpha lineage. Our findings provide a molecular explanation for an adaptation process leading to generation of the hyperactive AR subtype after TSGD.